Surgical management of suspected paraneoplastic myasthenia gravis in rectal cancer during neoadjuvant immunotherapy: a case report - Xia, Zhiyuan; Chen, Haining; Qiu, Ming; Huang, Wei; Li, Hui; Lin, Minglin; Zhang, Sen (Frontiers in Oncology, 2025)
Colorectal cancer is among the most common malignancies of the gastrointestinal tract. Immune checkpoint inhibitors (ICIs) have become a key component in the treatment of locally advanced rectal cancer (LARC), offering promising therapeutic outcomes. However, ICIs can occasionally cause significant adverse effects. Herein, we report a case of rectal cancer with suspected paraneoplastic myasthenia gravis (pMG) induced by immune checkpoint inhibitors (ICIs). Unfortunately, the patient lacked anti-acetylcholine receptor (AChR)/muscle-specific kinase (MuSK) antibody testing and muscle biopsy, which precluded a definitive diagnosis of pMG. Remarkably, following surgical resection, the patient not only achieved complete tumor eradication but also experienced full remission of myasthenia gravis (MG).